Evaluation of Factors for Conversion of Laparoscopic to Open Cholecystectomy in a Tertiary Care Center - Sujoy Mukherjee; Jagadamba Sharan; Rishi Jindal (International Journal of Anatomy Radiology and Surgery, 2018)
Introduction: Laparoscopic cholecystectomy is the treatment of choice for gall bladder diseases. Sometimes it has to be converted to open surgery because of various reasons. Aim: To evaluate and analyse the various factors leading to conversion of laparoscopic cholecystectomy to open cholecystectomy in cases of cholecystitis with cholelithiasis. Materials and Methods: A total of 505 laparoscopic cholecystectomies were attempted in Rohilkhand Medical College Bareilly, India from September 2014 to August 2015. Of these 37 (7.3%) were converted to open cholecystectomy. An analysis of different factors were made that lead to conversion. Result: About 7.3% of the total surgeries required conversion. Male patients were more prone for conversion (12.3%) as compared to females (4.9%). The most common intraoperative finding that lead to conversion was adhesions in 23 out of 37 (62.1%). These converted patients were found to have more chances of injuries the common bile duct and bowel and post-operative infections. Conclusion: Male patient and intraoperative findings of adhesions lead to the highest possibility of conversion of laparoscopic to open cholecystectomy. Knowledge of these factors helps in better preoperative counseling of patients as well as proper surgical planning.